Regulation of the Movement of Workers: Freedom of Passage Within the United States - Ivan C. Rutledge (Washington University Law Quarterly, 1953)
While it may be generally observed that within the jurisdiction of the United States there are few direct legal barriers to movement from one place to another, nevertheless it is actually a matter of speculation to a large degree what are the constitutional bases for protection and enforcement of this freedom. So far as research for this study discloses, the freedom to migrate for employment is not separately protected but is only part of the general freedom of locomotion. There are four avenues of approach to constitutional right that might include the right to migrate for employment. They are the privileges and immunities of citizens in the several states, the privileges and immunities of citizens of the United States, the power of Congress to regulate commerce, and the protections against deprivation of liberty without due process of law and against the denial of the equal protection of the laws. The full extent of the Thirteenth Amendment has not been defined, either in legislation or judicial construction, but to the extent that it protects against deprivation of choice of employment it removes the initial obstacle to search for a chosen employment.
Keywords: Civil rights; Labor law; Constitutional law: U. S. -- V. Personal; Civil and Political Rights